Paul Abbott - Johnson, Beth, 1980- (Television series (Manchester, England), 2013)
Creator of television series such as Shameless, Clocking Off, State of Play, Reckless, Linda Green and Children's Ward, Paul Abbott is a British producer and writer whose name and reputation for edgy, intelligent, successful and socio-political programmes holds significant weight in the contemporary television industry and with the public. This is the first book-length academic study of the television programmes created, written by, and/or executive-produced, by Abbott. It is also the first academic study to attempt to consider his complete oeuvre. Within a broadly chronological structure this volume elucidates, decodes and evaluates key examples of Abbott's output, exhibiting a vital evaluation of Abbott's work over the past three decades and assessing his contribution to British television. Primarily, the volume presents an aesthetic analysis of televisual case studies. The case studies explore the technicity or 'grammar' of the televisual, including: colour, sound, diegetic and non-diegetic music, point of view, shot size, shot length, dialogue, the creation of space and place, on-location shooting, temporality, televisual narrative, performance and mise-en-scène. The disclosures of the close textual analysis are to be associated with a range of thematic, stylistic and representational motifs across the range of Abbott's work, thereby inaugurating discussions based upon the 'authorial voice', definitions of 'quality' television and the negotiation of generic boundaries. Engaging with thematic and ideological notions of the personal, the autobiographical, the honest, the shameless, the pleasurable and the painful recourse of the specificity of 'ordinary life', the volume seeks to combine close textual analysis of Abbott's work with archival research and specially commissioned interviews with Abbott and other important industry practitioners.